Legal Concept of Sport - A. V. Iglin (Сибирское юридическое обозрение, 2018)
The relevance of the article is due to the complex nature of sports as a factor in influencing statehood, public relations, as well as the objective need for comprehensive legal regulation of mass and high-end sports, taking into account national and international legal doctrine and practice. It emphasizes the need to integrate sports and legal norms and rules into the legal system of states. At the same time, it is necessary to create a stable law and order in physical culture and sports on the basis of theoretical and legal knowledge of the relevant relations. Currently, it is difficult to overestimate the importance of sports law as a regulator of complex sports relations, as well as the need to study its theoretical and methodological attributes: aspects, ideas, sources, concepts, principles, problems that have been the subject of this work.